LEM domain containing 1 promotes pancreatic cancer growth and metastasis by p53 and mTORC1 signaling pathway. Issue 3 (1st March 2022) - Cao, Xiang; Yao, Na; Zhao, Zidan; Fu, Yue; Hu, Yuting; Zhu, Ping; Shi, Weihai; Tang, Liming
ABSTRACT: Pancreatic cancer (PC) is a common type of malignancy originating from the epithelium of the pancreatic duct, with the most lethal feature and worst prognosis. LEM domain containing 1 (LEMD1) is overexpressed in multiple tumor tissues and plays a key role in cancer carcinogenesis and progression. However, little is known about the potential of LEMD1 in PC. In this study, we explored the clinical values, as well as the potential roles and mechanisms of LEMD1 in PC. We, for the first time, showed that LEMD1 was upregulated in PC and negatively correlated with the overall and disease-free survival of patients with PC. Of the function, LEMD1 knockdown inhibited cancer cell growth, migration and invasion, while LEMD1 overexpression promoted tumor aggressiveness. The tumor-promoting influences of LEMD1 in PC were also proved by in vivo assays. Mechanistically, GSEA identified that LEMD1 promoted PC aggressiveness, as well as affecting cell cycle dysregulation and apoptosis resistance, by p53 suppression and the activation of the mTORC1 signal pathway. In short, LEMD1 could serve as a valuable prognostic candidate and a potential therapeutic target of PC. Abbreviations : ATCC: American Type Culture Collection; CCK-8: Cell counting kit 8; CDK: Cyclin-dependent kinases; CTA: Cancer-testis antigen; DMEM: Dulbecco's Modified Eagle's Medium; ECL: enhanced chemiluminescence; FBS: Fetal bovine serum; GEO: Gene Expression Omnibus; LEMD1: LEM domain containing 1; mTOR: mammalian target of rapamycin; NC: Negative control; PC: Pancreatic cancer; PVDF: Polyvinylidene difluoride membranes; qRT-PCR: Quantitative real-time polymerase chain reaction; SDS-PAGE: Sodium dodecyl sulfate polyacrylamide gel electrophoresis; SD: Standard deviation; SKP2: S-Phase kinase-associated protein 2; TAA: Tumor-associated antigen; TBST: Tris-buffered Saline Tween-20; TCGA: The Cancer Genome Atlas. Graphical abstract: uf0001